EQUIVARIANT GENERALIZATION OF FREUDENTHAL’S THEOREM. EQUIVARIANT n-MOBILITY - Gevorgian, P. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2025)
In the given paper the equivariant analogue of Freudenthal’s theorem in finite G-group is proved, which allows to generalize some results attained by Bogaty on n-mobility of topological distance.